2013
DOI: 10.1186/scrt159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravenous administration of allogenic bone marrow- and adipose tissue-derived mesenchymal stem cells on functional recovery and brain repair markers in experimental ischemic stroke

Abstract: IntroductionStem cell therapy can promote good recovery from stroke. Several studies have demonstrated that mesenchymal stem cells (MSC) are safe and effective. However, more information regarding appropriate cell type is needed from animal model. This study was targeted at analyzing the effects in ischemic stroke of acute intravenous (i.v.) administration of allogenic bone marrow- (BM-MSC) and adipose-derived-stem cells (AD-MSC) on functional evaluation results and brain repair markers.MethodsAllogenic MSC (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
208
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(226 citation statements)
references
References 44 publications
17
208
1
Order By: Relevance
“…In the current study, significantly increased levels of GFAP were noted in the striatum after cerebral I/R injury, and these levels then decreased with intravenous administration of HUMSCs. This finding agrees with the results of previous studies using other types of MSCs (16,18).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In the current study, significantly increased levels of GFAP were noted in the striatum after cerebral I/R injury, and these levels then decreased with intravenous administration of HUMSCs. This finding agrees with the results of previous studies using other types of MSCs (16,18).…”
Section: Discussionsupporting
confidence: 83%
“…The current results agree with those of previous studies reporting increases in cellular proliferation after AD-MSC and BM-MSC administration (18,23). In line with earlier studies, a later study found that, compared to infarction alone, administration of MSCs promoted cellular proliferation in SVZ and cell differentiation into neuroblasts in peri- Since there was no migration and implantation of HUMSCs in rats treated with HUMSCs, endogenous neural regeneration was studied using immunofluorescence double staining with neurofilament 200 (NF200) and BrdU in brain sections 14 d after surgery.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This could make AMSCs more effective than BMSCs in treatment of diabetes, especially the T-cell-mediated autoimmune type I diabetes. In addition, AMSCs were known by their safety, efficacy, abundance and ease harvesting and obtaining from discarded adipose tissue during surgery without ethical debate [48,49] .…”
Section: Streptozotocin Was Reported In Previous Studiesmentioning
confidence: 99%